Pengaruh Pendidikan di Sekolah dan Pendidikan Orang Tua di Rumah Terhadap Perilaku Siswa Pada Siswa MA Al-Kholil NU Berau - Hanafi; Munawir; Abdul Haris; Muhammad Alfi Syahrin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to determine the influence of school education and parental education at home on students’ behavior at MA Al-Kholil NU Berau. The research employed a quantitative approach using a survey method. The sample consisted of 55 students selected through purposive sampling technique. Data were collected using Likert-scale questionnaires that had been tested for validity and reliability. Data analysis employed multiple linear regression analysis using SPSS version 25. The results revealed that school education significantly influenced students’ behavior with a t-value of 3.214 and significance level of 0.002 < 0.05. Parental education at home also significantly influenced students’ behavior with a t-value of 4.126 and significance level of 0.000 < 0.05. Simultaneously, school education and parental education significantly affected students’ behavior with an F-value of 28.451 and significance level of 0.000 < 0.05. The coefficient of determination (R²) was 0.523, indicating that 52.3% of students’ behavior was influenced by school education and parental education, while the remaining percentage was influenced by other factors outside this study. This study confirms the importance of synergy between school and family education in shaping positive student behavior.